Intensity dependence of auditory P2 in monozygotic twins discordant for Vietnam combat: Associations with posttraumatic stress disorder - Metzger, Linda J. (2008)
Two studies have reported decreased intensity dependence of the P2 event-related potential (ERP) in male combat veterans with posttraumatic stress disorder (PTSD), a response pattern presumed to reflect central nervous system-induced protective inhibition and heightened central serotonergic activity. We used an identical twin, case-control design to investigate whether intensity dependence abnormalities reflect pretrauma vulnerability or are an acquired consequence of PTSD. ERPs were measured in male Vietnam combat veterans and their noncombat-exposed monozygotic twin brothers during a four-tone, stimulus-intensity modulation procedure. Contrary to previous findings in male veterans, the PTSD group had significantly steeper P2 amplitude intensity slopes, similar to those reported for female veterans and abused children with PTSD. Additionally, increased P2 amplitude intensity slope was associated with increased PTSD symptom severity, particularly the severity of reexperiencing symptoms. A mixed-model, random-effects analysis that included the combat-unexposed twins revealed a significant diagnosis by combat exposure interaction. Inspection of group means suggests that the observed increased P2 intensity dependence is a consequence of PTSD. Our findings further suggest that low serotonergic tone may emerge as one potential consequence of this disorder.